ANALYSIS OF RELIGIOUS VALUES IN THE FILM TEARS AT THE END OF THE PRAYER MAT: a SOCIOLOGICAL STUDY OG LITERATURE - Dewi, Lusi Cantika; utamy, Auliana; Berutu, Aisyah Tusyakdiah; Azzahra, Athiyya (Program Studi Pendidikan Bahasa Indonesia FKIP-UNIVA Medan, 2023)
This article describes the religious values represented in the film “Tears at the Edge of the Prayer Mat”. The research was conducted using a qualitative approach. The data source in the research is film. The focus of the research includes religious values relating to humans with God, other humans and nature and the relevance of religious values in learning literary works in schools. It is hoped that these two aspects of focus will be able to complement the religious values that are currently being abandoned by many people and the younger generation. It is hoped that the research will be able to remind all people to always embody religious values in their daily lives. The religious values found in this study include being patient as a human being, having steadfast morals, and being a just, sincere and useful human being. There is a relationship between learning and religious values which can be a guide for improving the character of school students.